Legal Protection for Taxpayers in Tax Dispute Resolution in the Tax Court - Larasati Ritonga; Isnaina Rizkia Ritonga; Alwiansyah; Alrihsan Hakim; Farhan Lubis (ISNU Sumatera Utara, 2025)
Taxes are the main source of state revenue that is important in supporting development and governance. In the Indonesian legal system, tax obligations are strictly regulated and involve the rights and obligations of taxpayers, which often lead to disputes with tax authorities. The main problem in this study is how legal protection can be provided to taxpayers during the dispute resolution process in the Tax Court. This research uses a normative legal approach with a literature study method, analyzes positive legal norms, and examines related regulations such as the Tax Court Law and KUP. The results of the study show that legal protection is not only limited to formal channels, but also includes taxpayers' procedural rights during trials, including the right to submit evidence and be accompanied by a lawyer. However, practice in the field shows that there are obstacles, such as lack of information and the length of the completion process. Recommendations are given to increase the effectiveness of the taxpayer rights protection system to be more fair and responsive in dealing with tax disputes.